MOTHER’S KNOWLEDGE DAN ATTITUDE ABOUT STUNTING OF CHILDREN IN NAMORAMBE DISTRIC - Siti Saidah Nasution; Febrina Oktavinola; Hariati (Talenta Publisher, 2019)
Stunting was associated by chronic malnutrition due to intake of nutrients that are lacking in a long time in children. This condition causes the child to have a height tends to be short in his age. The incidence of stunting is influenced by care in the family, especially related to the knowledge and attitudes of mothers in the event of stunting. Treatment from pregnancy to child is related to the fulfillment of food and family nutrition. This research is descriptive which aims to describe the knowledge and attitudes of mothers in the incidence of stunting in children. Population of all mothers with babies and toddlers in Namo Rambe sub-district. Samples are families / parents who have children aged one to 5 years. Data collection uses a questionnaire, which consists of demographic data, data on mother's knowledge and attitudes. Univariate data analysis uses the frequency of distribution and presentation. The results of mother's knowledge about stunting in general are in the low category at around 50.7%. The mother's attitude is in the negative attitude which is around 55.8%. Health workers must be able to optimize their role in providing health education to the community specifically about stunting.